2009
DOI: 10.1210/jc.2009-1369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Mass Index on Peak Growth Hormone Response to Provocative Testing in Children with Short Stature

Abstract: In children with short stature, BMI affects peak stimulated GH and should be considered when interpreting GH testing. Higher BMI SDS, even within the normal range, may lead to overdiagnosis of GH deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
65
5
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 27 publications
14
65
5
6
Order By: Relevance
“…Furthermore, a negative correlation was found between GH peak response to the combined test and BMI and BMI SDS, suggesting that BMI influences GH response to provocative tests, as reported in non-PWS subjects [34,35,36,37]. In our PWS cohort only 2 patients were obese.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, a negative correlation was found between GH peak response to the combined test and BMI and BMI SDS, suggesting that BMI influences GH response to provocative tests, as reported in non-PWS subjects [34,35,36,37]. In our PWS cohort only 2 patients were obese.…”
Section: Discussionsupporting
confidence: 62%
“…In another study by Albertsson-Wikland et al [20], the GH secretion rate correlated negatively with weight for height expressed in SDS in pubertal children. Stanley et al [21] demonstrated that higher BMI was associated with lower GH secretion in 116 children with short stature and suggested that the relationship between BMI and peak GH was not unique to obesity but rather persists in the normal-weight pediatric population. The pathogenesis of GH insufficiency in obesity is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Przy tym za ciężki niedobór GH (sGHD) u dziecka przyjmuje się zazwyczaj maksymalny wyrzut GH poniżej 5 ng/ml, a za częściowy niedobór GH (pGHD) maksymalny wyrzut GH pomiędzy 5 a 10 ng/ml [14][15][16]. Liczne doniesienia wskazują jednak na brak powtarzalności testów, co znacznie ogranicza ich wartość diagnostyczną [7,12,[17][18][19].…”
Section: Wstępunclassified
“…Wykonuje się określone badania laboratoryjne [5][6][7][8]26]. Różnorodność testów stymulujących wyrzut GH wskazuje na trudności z uzyskaniem powtarzalnych wyników, a także na niedoskonałość metod diagnostycznych [7,12,[17][18][19].…”
Section: Dyskusjaunclassified
See 1 more Smart Citation